Bangabandhu and Bangladesh, Sharif uddin Ahmed (ed.), (Dhaka: The University Press Limited and North South University 2021), - Rashid, Harun or (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
Abstract not available Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 147-152